2011
DOI: 10.1111/j.1600-0854.2011.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enlarged Lysosomes in beigej Cells Result From Decreased Lysosome Fission and Not Increased Lysosome Fusion

Abstract: Chediak-Higashi Syndrome is an autosomal recessive disorder that affects vesicle morphology. The Chs1/Lyst protein is a member of the BEACH family of proteins. The absence of Chs1/Lyst gives rise to enlarged lysosomes. Lysosome size is regulated by a balance between vesicle fusion and fission and can be reversibly altered by acidifying the cytoplasm using Acetate Ringer’s or by incubating with the drug vacuolin-1. We took advantage of these procedures to determine rates of lysosome fusion and fission in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 68 publications
(91 reference statements)
5
62
0
1
Order By: Relevance
“…Adding to the possible complexity of Lyst function are the findings of Durchfort (Durchfort et al, 2012). Although our comparative analyses have shown strong evidence that the LvsB mutant phenotype arises from inappropriate fusion, they presented strong evidence that the mouse Lyst homolog promotes fission from drug-induced enlarged endosomal compartments.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Adding to the possible complexity of Lyst function are the findings of Durchfort (Durchfort et al, 2012). Although our comparative analyses have shown strong evidence that the LvsB mutant phenotype arises from inappropriate fusion, they presented strong evidence that the mouse Lyst homolog promotes fission from drug-induced enlarged endosomal compartments.…”
Section: Discussionmentioning
confidence: 90%
“…The fission model for Lyst and LvsB function predicts that the delayed maturation of lysosomes should cause an increase in vesicle size at the stage where maturation is delayed (Durchfort et al, 2012). Delaying the maturation of lysosomes is predicted to allow the continued flow of endosomes that are competent to undergo homotypic fusion.…”
Section: Formation Of Hybrid Lysosomal Compartments In Lvsb-null Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the LYST protein that give rise to CHS have been suggested to cause a fission defect that entails the formation of enlarged lysosomes, whose excessive size appears to prevent fusion at the immune synapse (Baetz et al, 1995;Durchfort et al, 2012). A recent report shows that overexpression of either Rab27a alone or Rab27a together with Slp3 (also known as SYTL3) partially restores granule secretion [measured by appearance of the lysosomal membrane protein CD107a (also known as LAMP1) at the cell surface] and that coexpression of Rab27a, Munc13-4 and Slp3 rescues the secretion defect of CHS CTLs.…”
Section: Targeted Granule Secretion At the Immune Synapsementioning
confidence: 99%
“…Mutations that perturb this process, for example, mutations in the Chediak-Higashi syndrome/ lysosomal trafficking regulator (CHS/Lyst) in humans, with the Chediak-Higashi syndrome, and in beige (Lyst bg /Lyst bg ) mice (Durchfort et al, 2012) result in giant SGs and can cause significant pathology. Indeed, we have shown that the same phenotype of increased sized SGs is caused by knockdown of synaptotagmin 3, a member of the synaptotagmin family of traffic regulating proteins (Grimberg et al, 2003) that regulates endocytic recycling (Grimberg et al,…”
Section: Recycling Of Sgsmentioning
confidence: 99%